Speech Functions Used by Speakers in Allison L. Randallâ€™s Short Story â€œEnd of the Lineâ€ - Ely Fathonah; Sri Mulatsih (Universitas Dian Nuswantoro, 2018)
Abstract. Conversation is a process of exchanging two variables, there are speech role and commodity exchange, the combination between them is called speech function. This thesis is entitled â€œSpeech Function Used by All Speaker In Allison L. Randallâ€˜s Short Story End of The Lineâ€. This study aims at describing the kinds of speech function and interpersonal role created by all speakers in Allison L. Randallâ€™s short story â€œEnd of The Lineâ€. They are Liza, Frank, Noah Crawford, Postmaster, Zedekiah Smith and Caleb. This study used qualitative researchÂ Â method. Qualitative research methodÂ was used to collect and analyze data that cannot be represented by number. Descriptive research was used in the literal sense of describing situation and event. The result of this study shows that there are 10 kinds of speech functions produced by all characters (Liza, Frank, Noah Crawford, Postmaster, Zedekiah Smith and Caleb). They are 11 statements, 8 commands, 5 offers, 7 questions, 2 acknowledgements, 3 contradictions, 2 acceptances, 2 rejections, 2 answers, and 2 disclaimers. The highest speech function is â€˜commandâ€™ produced by Liza because she demands the bank robber to release her from the captive. She also produced highest speech function â€˜questionâ€™, because she is the main character. She is a talkative who wants to know everything. The highest speech function produced by Zedekiah Smith is â€˜statementâ€™ because he is bank robber who comes back again to release Liza.Keywords: Conversation, Short Story, Speech Function, UtterancesAbstrak. Percakapan adalah proses perubahan 2 variabel, yaitu peran berbicara dan perpindahan peran. Kombinasi di antara keduanya disebut fungs tutur. Penelitian in iberjudul Fungsi Tutur yang digunakan oleh Seluruh Karakter Pada Cerita Pendek Allison L. Randall â€œEnd of The Line. Penelitian ini berhubungan dengan analisis fungsi tutur fokus pada ujaran yang digunakan oleh semua karakter pada cerita pendek Allison L. Randall â€œEnd of The Lineâ€. Mereka adalah Liza, Frank, Noah Crawford, Kepala kantor Pos, Zedekiah Smith, dan Caleb. Penelitian ini menggunakan metode penelitian kualitatif. Metode penelitian kualitatifÂ digunakanÂ untukÂ menyeleksiÂ danÂ menganalisaÂ dataÂ yangÂ tidakÂ dapat dipresentasikan dengan angka. Penelitian ini juga menggunakan metode deskripsi. Metode deskripsi digunakan untuk mendeskripsikan situasi dan peristiwa. Hasil penelitian Â menunjukkan bahwa 10 jenis ujaran yang dibuat oleh semua karakter di dalam cerita pendek (Liza, Frank, Noah Crawford, Kepala Kantor post, Zedekiah Smith, dan Caleb) adalah 11 pernyataan, 8 perintah, 5 penawaran, 7 pertanyaan, 2 pengakuan,3 kontradiksi ,2 penerimaan, 2 penampikan, 2 jawaban, 2 penyangkalan. Pelaku yang paling banyak menghasilkan fungsi tutur perintah adalah Liza karena Liza meminta kepada perampok untuk dibebaskan dari sekapanya. Dia juga paling banyak menghasilkan fungsi tutur pertanyaan karena dia adalah peran utama di dalam cerita. Pelaku yang paling banyak menggunakan fungsi tutur pernyataan adalah Zedekiah Smith, dia adalah perampok bank yang kembali untuk menyelamatkan Liza. Kata kunci : cerita pendek, fungsi tutur, percakapan, ujaran